Psychological and structural bias in civil jury awards. Issue 4 (10th October 2016) - Girvan, Erik; Marek, Heather J.
Abstract : Purpose: The purpose of this paper is twofold. First, it proposes a basic organizing framework for when a plaintiff's race, ethnicity, or sex may impact civil jury awards. The framework takes into account psychological and structural sources of bias and the ways in which they may interact when jurors have more or less discretion. Second, the paper employs a methodological innovation to overcome one of the primary barriers to empirical field research on bias in civil legal decisions: the absence of plaintiff demographic information. Design/methodology/approach: The data set is comprised of jury verdicts in tort cases combined with information from the US Census Bureau regarding race and ethnicity. Statistical tests measure the relationships between race, ethnicity, sex, and awards for economic damages and pain and suffering. Findings: Overall, the results were consistent with the psycho-structural framework. Where jurors had discretion (i.e. pain and suffering damages), they awarded less to black plaintiffs than to white plaintiffs, indicating potential psychological bias. Where jurors had little discretion (i.e. lost income) they awarded less to female plaintiffs and more to Asian plaintiffs than to male and white plaintiffs, respectively, a potential reflection of structural income disparities. Thus, the framework and method have promise for exploring relationships between structural and psychological bias and differential civil jury awards. Originality/value: Because demographic information is not easily available, there is very little research on race and gender bias in civil cases. This study introduces and provides a conceptual test of a novel framework for when bias is most likely to impact damage awards in these cases and tests it using advances in social demography that can help researchers overcome this barrier.